Flame-Retardancy Studies on Cotton Fabric by Application of Aluminium Phosphate - MORTEZA MOSTASHARI, SAYED; DARSARAEI, AZAM (Asian Journal of Chemistry, 2010)
In the present study, the effect of synthetic aluminium phosphate on the flammability of cotton fabric (plain 240 g/m2) has been reported. The suitable suspension of aluminium phosphate was prepared and each bunch of bone-dried, weighed fabrics had been dipped and stirred in the suspension baths. They were squeeze rolled and dried horizontally in an oven at 110ºC for 0.5 h. Afterwards the specimens were cooled in a desiccator and reweighed by an analytical balance. They were kept under ordinary conditions before the fulfillment of the vertical flame test. The optimum add-on values to impart flame and glow retardancy was about 30 g anhydrous aluminium phosphate per 100 g fabric. This action is assigned to be in favor of Condensed Phase Retardation ascribed in chemical theory. It is recommended to apply this salt in conjunction with other flame-retardants such as nitrogen compounds to gain a spectacular synergistic performance.